Prevalence and Frequency of Online Sexual Activity by Adults With Autism Spectrum Disorder. (September 2019) - Byers, E. Sandra; Nichols, Shana
We examined the prevalence and frequency with which cognitively able adults (141 men, 190 women) with autism spectrum disorder (CA-ASD) engaged in a range of online sexual activities (OSAs). Participants completed an online survey that assessed their recent involvement in nonarousal (Information Seeking, Chatting), solitary-arousal (S-OSA), and partnered-arousal (P-OSA) online sexual activities. Almost two thirds had engaged in one or more OSA but, on average, had done so infrequently. There were only a few differences based on sex, age, and sexual identity. Significantly more men than women had engaged in Information Seeking and S-OSA and had done so more frequently. Individuals in their 20s were significantly more likely to have engaged in Information Seeking. Sexual-minority individuals were more likely to report engaging in P-OSA than were heterosexual individuals. These results are discussed in terms of their implications for sexuality education aimed at assisting adults with CA-ASD to establish a healthy and meaningful sexuality.